The little stranger [videorecording (DVD)] - Gleeson, Domhnall, 1983-; Wilson, Ruth, 1982-; Poulter, Will; Rampling, Charlotte, 1946- (Universal Pictures Home Entertainment, 2018)
The story of Dr. Faraday, the son of a housemaid, who has built a life of quiet respectability as a country doctor. During the long hot summer of 1948, he is called to a patient at Hundreds Hall, where his mother once worked. But it is now in decline and its inhabitants, a mother, son, and daughter, are haunted by something more ominous than a dying way of life. When he takes on his new patient, Faraday has no idea how closely the family's story is about to become entwined with his own.